Modelling and Analysis of the Simple Water Heater System - Haresh A. Suthar; Jagrut J. Gadit (Institute of Advanced Engineering and Science, 2011)
Modelling is nothing but converting physical information in to mathematical form. Mathematical model plays vital role for identification and analysis of the system. In this paper simple water heater system was taken as test bench. Considering system parameters mathematical model of first order with time delayed was derived. Model was simulated in the simulation tool MATLAB and systems response has been studied by changing various parameters like static gain, time constant, delay time and noise, for applied step input.Response of the simulated system was analysed and compare with the actual real time system parameters. Keywords: Modelling, Analysis, MATLAB, Water heater system.DOI:http://dx.doi.org/10.11591/ijece.v1i1.59